Nivolumab and Ipilimumab in Metastatic Uveal Melanoma: Results From a Single-Arm Phase II Study. Issue 6 (20th February 2021) - Pelster, Meredith S.; Gruschkus, Stephen K.; Bassett, Roland; Gombos, Dan S.; Shephard, Michael; Posada, Liberty; Glover, Maura S.; Simien, Rinata; Diab, Adi; Hwu, Patrick; Carter, Brett W.; Patel, Sapna P.
Abstract : PURPOSE: Metastatic uveal melanoma has poor overall survival (OS) and no approved systemic therapy options. Studies of single-agent immunotherapy regimens have shown minimal benefit. There is the potential for improved responses with the use of combination immunotherapy. PATIENTS AND METHODS: We conducted a phase II study of nivolumab with ipilimumab in patients with metastatic uveal melanoma. Any number of prior treatments was permitted. Patients received nivolumab 1 mg/kg and ipilimumab 3 mg/kg for four cycles, followed by nivolumab maintenance therapy for up to 2 years. The primary outcome of the study was overall response rate (ORR) as determined by RECIST 1.1 criteria. Progression-free survival (PFS), OS, and adverse events were also assessed. RESULTS: Thirty-five patients were enrolled, and 33 patients were evaluable for efficacy. The ORR was 18%, including one confirmed complete response and five confirmed partial responses. The median PFS was 5.5 months (95% CI, 3.4 to 9.5 months), and the median OS was 19.1 months (95% CI, 9.6 months to NR). Forty percent of patients experienced a grade 3-4 treatment-related adverse event. CONCLUSION: The combination regimen of nivolumab plus ipilimumab demonstrates activity in metastatic uveal melanoma, with deep and sustained confirmed responses.